Factors Influencing Saudi Investors’ Perceptions and Preferences for Mutual Funds vs. Direct Investment in the Financial Market - Khababa, Nourredine (Journal of Ecohumanism, 2024)
This study explores the preferences of Saudi investors regarding mutual investment funds versus direct market investments, based on a sample of 881 individual investors. It examines demographic factors such as age, gender, occupation, education, investment size, and financial market experience to understand motivations for choosing or avoiding mutual funds. The study highlights the perceived benefits of professional management, risk diversification, and Sharia compliance, while also addressing concerns like high fees, lack of transparency, and unclear strategies. A quantitative methodology was used, employing a structured questionnaire to gather data. The questionnaire, designed with a Likert scale, measured investor attitudes and motivations. Descriptive statistics, cross-tabulation, and the Chi-square test (X²) were utilized to analyze relationships between demographics and investment preferences, providing insights into the significant associations between investor characteristics and their investment decisions. Key findings indicate that older and less experienced investors favor mutual funds due to convenience and limited financial knowledge, while more experienced investors prefer direct investments for higher returns and control. The study suggests that addressing transparency and cost concerns, along with enhancing financial education, could improve the appeal of mutual funds in Saudi Arabia. As the Kingdom advances its Vision 2030 goals, promoting financial literacy and offering diversified investment options will be essential for balancing investor preferences and fostering a more inclusive financial market.